Does extreme rainfall lead to heavy losses in the food industry?. Issue 2 (3rd June 2019) - Lucas, Edimilson Costa; Mendes-Da-Silva, Wesley; Araujo, Gustavo Silva
Abstract : Purpose: Managing the risks associated to world food production is an important challenge for governments. A range of factors, among them extreme weather events, has threatened food production in recent years. The purpose of this paper is to analyse the impact of extreme rainfall events on the food industry in Brazil, a prominent player in this industry. Design/methodology/approach: The authors use the AR-GARCH-GPD hybrid methodology to identify whether extreme rainfall affects the stock price of food companies. To do so, the authors collected the daily closing price of the 16 food industry companies listed on the Brazilian stock exchange (B3), in January 2015. Findings: The results indicate that these events have a significant impact on stock returns: on more than half of the days immediately following the heavy rain that fell between 28 February 2005 and 30 December 2014, returns were significantly low, leading to average daily losses of 1.97 per cent. These results point to the relevance of the need for instruments to hedge against weather risk, particularly in the food industry. Originality/value: Given that extreme weather events have been occurring more and more frequently, financial literature has documented attempts at assessing the economic impacts of weather changes. There is little research, however, into assessing the impacts of these events at corporate level. Abstract : Propósito: O gerenciamento de riscos associados à produção mundial de alimentos é um desafio importante para governantes. Diversos fatores, entre eles os eventos climáticos extremos, têm ameaçado a produção de alimentos nos últimos anos. Neste artigo nós analisamos o impacto de eventos de chuvas extremas na indústria de alimentos no Brasil, um dos maiores produtores mundiais. Diseño/metodología/enfoque: Empregamos a metodologia híbrida AR-GARCH-GPD para verificar se chuvas extremas afetam o preço das ações das empresas de alimentos. Para isso, coletamos os preços de fechamento diário de 16 empresas do setor de alimentos listadas na Bolsa de Valores do Brasil [B] 3, em janeiro de 2015. Resultados: Os resultados sugerem que esses eventos exercem impacto significante sobre o retorno das ações: em mais da metade dos dias imediatamente posteriores à chuva extrema ocorrida entre 28/02/2005 e 30/12/2014, os retornos foram significantemente baixos, levando a perdas médias diárias próximas de 1, 97%. Esses resultados apontam para a relevância da necessidade de instrumentos para proteção contra riscos climáticos, particularmente na indústria de alimentos. Originalidad/valor: Tendo em vista que eventos climáticos extremos têm ocorrido com uma frequência cada vez maior, a literatura de finanças tem documentado tentativas de avaliar os impactos econômicos das mudanças climáticas. No entanto, nota-se a carência de pesquisas para avaliar os impactos desses eventos no nível das empresas.